Woodflour as Reinforcement of Polypropylene - Caraschi, José Cláudio; Leão, Alcides Lopes [UNESP] (ABM, ABC, ABPol, 2002)
The effect of the filler content and size, as well as accelerated aging on the mechanical properties of polypropylene composites reinforced with woodflour (WF/PP) were evaluated. The composites were prepared by the extrusion of polypropylene with woodflour (Pinus elliotti) based on following ratios: 15, 25 and 40 wt% with two different granulometries. The specimens were injection molded according to ASTM standards. The composite properties did not show significant differences as a function of the filler granulometry. We also observed that by increasing the filler content, both the mechanical properties and the melt flow index (MFI) decreased, and the elasticity modulus, hardness and density increased. Concerning the accelerated aging, the composite presented a reduction in tensile properties. The results showed that the composite properties are extremely favorable when compared to other commercial systems reinforced by inorganic fillers.
Keywords: composites; polypropylene; woodflour and mechanical properties